2020
DOI: 10.1177/1352458520923945
|View full text |Cite
|
Sign up to set email alerts
|

Frailty in ageing persons with multiple sclerosis

Abstract: Background: Recent progress in multiple sclerosis (MS) management has contributed to a greater life expectancy in persons with MS. Ageing with MS comes with unique challenges and bears the potential to greatly affect quality of life and socioeconomic burden. Objectives: To compare frailty in ageing persons with multiple sclerosis (pwMS) and controls; to correlate frailty with MS clinical characteristics. Methods: PwMS and controls over 50 years old were recruited in a cross-sectional study. Two validated frail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
1
21
3
Order By: Relevance
“…Frailty was found to be associated with major phenotypic characteristics of MS. FI values were positively correlated with EDSS scores and frail MS patients exhibited greater disability relative to fitter participants. These findings confirm and expand the recent evidence provided by Ayrignac et al 10 obtained in a sample of older patients (mean age = 58.5 ± 6 years) with MS. Frailty was also associated with higher levels of fatigue, one of the most frequent and disabling symptoms in MS patients. 21 Fatigue is defined by the Multiple Sclerosis Council for Clinical Practice Guideline as 'a subjective lack of physical and/or mental energy that is perceived by the individual or caregiver to interfere with usual and desired activities'.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Frailty was found to be associated with major phenotypic characteristics of MS. FI values were positively correlated with EDSS scores and frail MS patients exhibited greater disability relative to fitter participants. These findings confirm and expand the recent evidence provided by Ayrignac et al 10 obtained in a sample of older patients (mean age = 58.5 ± 6 years) with MS. Frailty was also associated with higher levels of fatigue, one of the most frequent and disabling symptoms in MS patients. 21 Fatigue is defined by the Multiple Sclerosis Council for Clinical Practice Guideline as 'a subjective lack of physical and/or mental energy that is perceived by the individual or caregiver to interfere with usual and desired activities'.…”
Section: Discussionsupporting
confidence: 92%
“…In a recent monocentric cross-sectional study, Ayrignac et al 10 used the FI to assess frailty in 80 older patients with MS and 37 age-matched healthy controls (HCs). The authors included only over 50 years old subjects and observed that patients were more 'frail' than HCs.…”
Section: Introductionmentioning
confidence: 99%
“… 41 In persons with MS, disability is strongly associated with frailty. 42 Our disability measure aimed to capture individuals with poor performance status according to their use of home care and long-term care services; most individuals in such Canadian settings are frail. Although our exploratory analyses including disability as a covariate should be viewed cautiously due to the modest number of individuals affected and the focus on more severe forms of disability, they raise the possibility that disability mediates some of the association between MS and reduced survival in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is also some evidence indicating that dementia favors the occurrence of UI and FI [19]. Regarding overall health, a study including 117 participants showed that frailty was higher in the presence than in the absence of MS and that several variables predicted frailty in adults with this neurological disorder (e.g., expanded disability status scale [EDSS], education level, and disease duration) [23]. In turn, frailty was found to be significantly associated with an increase in the incidence of UI in a 12-month cohort of 210 elderly adults living in Singapore [22].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of 73 adults with MS from Australia revealed that approximately 31% of the sample reported occasional to daily UI, while the proportion of participants with frequent FI was around 14% [6]. The high prevalence of UI and FI in this neurological population may be explained by the demyelination of the neurons involved in the bladder and bowel function and also by several frequent comorbidities of MS (e.g., sarcopenia [17, 18] and dementia [19-21]) and a higher frailty risk [22, 23]. Although previous studies focusing on UI and FI in patients diagnosed with MS have advanced the field, these studies have some limitations that need to be acknowledged.…”
Section: Introductionmentioning
confidence: 99%